2015
DOI: 10.1016/j.ijepes.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Power system state estimation using a direct non-iterative method

Abstract: a b s t r a c tThis paper describes a new method for state estimation of a non-linear AC power system in a non-iterative manner. This method is based on the Kipnis-Shamir relinearization technique that is used to solve over-defined sets of polynomial equations. The technique transforms the equations to a higher dimensional linear space which allows the states to be solved in a non-iterative manner. Given accurate measurements, this new state estimation method provides the same results as traditional iterative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…This situation deteriorates the diagonal elements of the gain matrix, which are supposed to be dominant for a positive definite matrix. The effect of the R/X ratio on fast decoupled load flow studies of distribution grids has been reported previously due to the direct relation of the former with the coupling of (P-θ) and (Q -|U |) [2,26]. However, the Jacobian of the state estimator is built using measurement sets different from those used for load flow studies.…”
Section: High Ratio Of R/x In Distribution Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation deteriorates the diagonal elements of the gain matrix, which are supposed to be dominant for a positive definite matrix. The effect of the R/X ratio on fast decoupled load flow studies of distribution grids has been reported previously due to the direct relation of the former with the coupling of (P-θ) and (Q -|U |) [2,26]. However, the Jacobian of the state estimator is built using measurement sets different from those used for load flow studies.…”
Section: High Ratio Of R/x In Distribution Systemsmentioning
confidence: 99%
“…Figure 4 shows the SE variance of the 18-bus system before and after the regularization. Significant improvements can be noticed in the estimated states (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in addition to some minor improvements in the first 17 states. However, the total SE variance has dropped from 0.0092 to 0.0060.…”
Section: Reducing the Redundant Measurementsmentioning
confidence: 99%
“…Abbasi and Seifi [25] suggested a master-slave-splitting technique to estimate the state variables of global power system. State estimator algorithm using a direct non-iterative method was given in [26]. A probabilistic approach to power system state estimation was demonstrated in [27].…”
Section: Introductionmentioning
confidence: 99%
“…For examples, a three‐stage SE method based on the sequential solution of two WLS linear problems with a nonlinear explicit transformation has been presented . In Ref an interesting method which can directly obtain the solution of WLS‐SE without iteration has been proposed. Another WLS‐SE method which requires no iteration has also been presented .…”
Section: Introductionmentioning
confidence: 99%